Przewlekłe zapalenie brzegów powiek wywołane przez nużeńca Demodex folliculorum - Gerkowicz, Marek; Baltaziak, Lucyna; Puacz, Elżbieta (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Two cases of the very long term observation and clinical findings of chronic blepharitis caused by mite Demodex folliculorum are presented. Both patients were treated for over ten years for inflammation of the margin of the eyelid with antibiotics and steroids administered locally. A significant thickening of the blood vessels in the eyelid and numerous cylindrical cuffs of dry discharge around the base of the eyelashes persuaded us to carry out microbiological tests on the suspect eyelashes. In both cases we received additional test results from the epilated eyelashes. Demodex folliculorum should be taken into consideration as an etiological factor in cases of chronic blepharitis.